Separator Coating Composition
The separator coating composition, featuring a combination of water-soluble and water-insoluble polymers with specific particle structures, addresses the challenges of heat resistance, adhesion, breathability, and conductivity in lithium secondary battery separators, enhancing battery performance and safety.
Patent Information
- Application Number
- JP2023547588
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-05-27
- Filing Date
- 2022-03-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-03-07
AI Technical Summary
Existing separator coatings for lithium secondary batteries face challenges in achieving balanced heat resistance, adhesion, breathability, and conductivity, often resulting in reduced ion transfer paths and battery performance due to the closure of pores by ceramic particles or PVDF-based binders.
A separator coating composition comprising a water-soluble polymer and a water-insoluble polymer, with the water-insoluble polymer including solid particles and cyclic hollow particles, is used to create an adhesive layer that maintains breathability and conductivity while enhancing heat resistance and adhesion.
The proposed solution achieves balanced heat resistance, adhesion, breathability, and conductivity, thereby improving the charging and discharge performance of lithium secondary batteries and reducing the risk of internal short circuits and thermal runaway.
Smart Images

Figure 0007665033000004 
Figure 0007665033000005 
Figure 0007665033000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator coating composition, and more particularly to a separator coating composition that can impart electrode adhesion to the surface of a separator and effectively prevent air permeability from decreasing. [Background technology]
[0002] Lithium secondary batteries are widely used as power sources for various electrical products that require small size and light weight, such as smartphones, laptops, and tablet computers. As their application range expands to include smart grids and medium- to large-sized batteries for electric vehicles, there is a demand for the development of lithium secondary batteries that have large capacity, long life, and high stability.
[0003] As a means to achieve the above-mentioned objectives, there has been active research and development into separators with micropores that separate the positive and negative electrodes to prevent internal shorts and facilitate the movement of lithium ions during charging and discharging. In particular, there has been active research and development into microporous separators made of polyolefins such as polyethylene, which are advantageous in forming pores through thermally induced phase separation, are economical, and tend to satisfy the physical properties required for a separator.
[0004] However, separators made of polyethylene, which has a low melting point of about 135°C, can shrink and deform when heated by the heat generated by the battery at temperatures above its melting point. If such deformation causes a short circuit, it can lead to thermal runaway in the battery, which can cause safety issues such as fire.
[0005] In addition, polyolefin-based separators that have been widely used in the past have poor heat resistance and mechanical strength, and when exposed to a temperature of 150°C for about an hour, they experience a thermal shrinkage rate of 50 to 90%, causing the separator to lose its function and making it highly likely to cause an internal short circuit when subjected to external impact.To address these issues, a technology has been proposed in which the surface of the separator is coated with a heat-resistant layer containing ceramic particles.
[0006] However, such a heat-resistant layer has significant technical issues in relation to air permeability and conductivity (resistance), which are factors that have a significant effect on the performance of the separator. That is, when a heat-resistant layer containing ceramic particles is formed on the surface of a porous substrate, the heat resistance of the separator is improved, but the ceramic particles contained in the heat-resistant layer close the pores formed in the porous substrate, reducing the air permeability of the separator, which significantly reduces the ion transfer path between the positive and negative electrodes, resulting in a significant deterioration in the charge and discharge performance of the secondary battery. In addition, as the heat-resistant layer is continuously exposed to the electrolyte inside the battery, the ceramic particles are partially and continuously detached from the porous substrate, which may gradually reduce the heat resistance of the separator.
[0007] In addition, there have been attempts to improve the adhesive strength with the electrodes and the life characteristics of secondary batteries by further forming an adhesive layer containing a PVDF-HFP copolymer on a conventional polyolefin-based separator or heat-resistant layer in order to develop adhesive strength with the electrodes (Patent Document 1, etc.). However, such PVDF-based binders are also lipophilic substances and generally use volatile organic substances as solvents, which poses a problem of adverse effects on the health of workers during the coating and drying processes.
[0008] In response to this, an aqueous coating solution in which PVDF-based polymer particles are dispersed in water has been developed and applied. However, since the PVDF-based polymer particles remain in particulate form even after the coating solution is dried, the PVDF-based polymer particles contained in the adhesive layer, like the heat-resistant layer, close the pores formed in the porous substrate and / or the heat-resistant layer, reducing the air permeability of the separator. This significantly reduces the ion transfer paths between the positive and negative electrodes, resulting in a significant reduction in the charge and discharge performance of the secondary battery. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] Korean Patent Application No. 10-2012-0117249 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention has been made to solve the problems of the prior art as described above, and an object of the present invention is to provide an electrode adhesive separator coating composition that can achieve a balanced combination of heat resistance, adhesiveness, breathability, and conductivity, and a separator including the same. [Means for solving the problem]
[0011] One aspect of the present invention provides a separator coating composition comprising a water-soluble polymer and a water-insoluble polymer, the water-insoluble polymer comprising solid particles and annular hollow particles.
[0012] In one embodiment, the solid particles may have a core-shell structure comprising a core and a shell covering at least a portion of the surface of the core.
[0013] In one embodiment, the solid particles may include first solid particles having an average particle size of 0.3 μm or less and second solid particles having an average particle size of more than 0.3 μm.
[0014] In one embodiment, the annular hollow particles include an annular shell having a through-hole formed in a central portion, and the interior of the annular shell may include a filler and a hollow.
[0015] In one embodiment, the average diameter of the through-hole may be larger than the average particle size of the first solid particles.
[0016] In one embodiment, the proportion of the filler inside the annular shell may be 1 to 99% by volume.
[0017] In one embodiment, the content of the annular hollow particles in the water-insoluble polymer may be 10 to 50% by weight.
[0018] Another aspect of the present invention provides a separator including a porous base film and an adhesive layer located on at least one surface of the porous base film and made of the separator coating composition.
[0019] In one embodiment, the porous base film may include a porous substrate and a heat-resistant layer located on at least one surface of the porous substrate and including a plurality of inorganic particles bonded by a binder.
[0020] In one embodiment, the separator can satisfy one or more of the following conditions (i) to (v). (i) Fs ≤ 190 sec / 100 ml or less (Fs is the air permeability of the separator); (ii) Rs ≤ 100 mΩ (Rs is the resistance of the separator); (iii) the longitudinal thermal shrinkage rate at 150 °C is 2.5% or less; (iv) 0 sec / 100 ml < Fs - Fb ≤ 20 sec / 100 ml (Fb is the air permeability of the base film); (v) 0 mΩ < Rs - Rb ≤ 10 mΩ (Rb is the resistance of the base film).
Advantages of the Invention
[0021] The separator coating composition according to one aspect of the present invention includes a water-soluble polymer and a water-insoluble polymer, and a portion of the water-insoluble polymer is composed of annular hollow particles having a through hole formed in the center, thereby achieving a balanced combination of heat resistance, adhesion, breathability, and conductivity.
[0022] It should be understood that the effects of the present invention are not limited to the effects described above, but include all effects that can be inferred from the configuration of the invention described in the detailed description of the present invention or the claims. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is an SEM image of a separator coating composition according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a solid particle according to one embodiment of the present invention. [Diagram 3] FIG. 3 shows a plan view (FIG. 3(a)) and a cross-sectional view (FIG. 3(b)) of an annular hollow particle according to one embodiment of the present invention. [Figure 4] FIG. 4 is a SEM image of the coating compositions according to the examples of the present invention and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will be described below with reference to the accompanying drawings. However, the present invention can be realized in various different forms and is not limited to the embodiments described herein. In the drawings, in order to clearly explain the present invention, parts that are not related to the description are omitted, and similar parts are designated by similar reference numerals throughout the specification.
[0025] Throughout the specification, when any part is said to be "connected" to another part, this includes not only the case where it is "directly connected" to another part, but also the case where it is "indirectly connected" through another member in between. Furthermore, when any part is said to "include" a certain component, this does not mean that it excludes other components, but that it can further include other components, unless otherwise specified to the contrary.
[0026] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings.
[0027] One aspect of the present invention provides a separator coating composition comprising a water-soluble polymer and a water-insoluble polymer, wherein the water-insoluble polymer comprises solid particles and annular hollow particles.
[0028] 1 is a SEM image of a separator coating composition according to one embodiment of the present invention. Referring to FIG. 1, the separator coating composition includes a water-soluble polymer and a water-insoluble polymer, and the water-insoluble polymer may include solid particles 10 and annular hollow particles 20.
[0029] The term "water-insoluble polymer" as used herein means a polymer that does not dissolve in water and disperses or floats in water in the form of fine particles, and is called a latex, emulsion, etc. The water-insoluble polymer may be in the form of fine particles in the adhesive layer of the separator described below.
[0030] Meanwhile, the term "water-soluble polymer" as used herein means a polymer that dissolves in water and has properties that are not observed as particles, etc. The water-soluble polymer can be melted and fused in the adhesive layer of the separator described below to bond the water-insoluble polymer particles to each other as well as to bond the water-insoluble polymer particles to the porous base membrane.
[0031] In addition, the term "solid particle" as used herein means a particle whose interior is filled with a given substance without any voids, and the term "hollow particle" means a particle whose interior has a void of a given volume.
[0032] 2 is a cross-sectional view of a solid particle according to one embodiment of the present invention. Referring to FIG. 2, the solid particle 10 may have a core-shell structure including a core 11 and a shell 12 covering at least a portion, preferably the entire surface of the core.
[0033] Examples of the monomer constituting the polymer of the core 11 of the solid particle include vinyl chloride monomers such as vinyl chloride and vinylidene chloride; vinyl acetate monomers such as vinyl acetate; aromatic vinyl monomers such as styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene; vinylamine monomers such as vinylamine; vinylamide monomers such as N-vinylformamide and N-vinylacetamide; acid group-containing monomers such as monomers having a carboxylic acid group, monomers having a sulfonic acid group, monomers having a phosphoric acid group, and monomers having a hydroxyl group; (meth)acrylic acid derivatives such as 2-hydroxyethyl methacrylate; (meth)acrylic acid derivatives such as methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, and 2-ethylhexyl acrylate; ) acrylic acid ester monomers; (meth)acrylamide monomers such as acrylamide and methacrylamide; (meth)acrylonitrile monomers such as acrylonitrile and methacrylonitrile; fluorine-containing (meth)acrylate monomers such as 2-(perfluorohexyl)ethyl methacrylate and 2-(perfluorobutyl)ethyl acrylate; maleimide; maleimide derivatives such as phenylmaleimide; diene monomers such as 1,3-butadiene and isoprene; and combinations of two or more of these. The monomer may be one selected from the group consisting of (meth)acrylic acid ester monomers, (meth)acrylonitrile monomers, and more preferably (meth)acrylic acid ester monomers, but is not limited to these.
[0034] The polymer of the core 11 may also include an acid group-containing monomer, which may be, for example, one selected from the group consisting of a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphoric acid group-containing monomer, a hydroxyl group-containing monomer, and a combination of two or more of these, but is not limited thereto.
[0035] The carboxylic acid group-containing monomer may be, for example, a monocarboxylic acid, a dicarboxylic acid, etc., the monocarboxylic acid may be acrylic acid, methacrylic acid, crotonic acid, etc., and the dicarboxylic acid may be maleic acid, fumaric acid, itaconic acid, etc.
[0036] The sulfonic acid group-containing monomer may be, for example, vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and the like.
[0037] The phosphate group-containing monomer may be, for example, 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, ethyl-(meth)acryloyloxyethyl phosphate, and the like.
[0038] The hydroxyl group-containing monomer may be, for example, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, and the like.
[0039] The polymer of the core 11 may further include a crosslinkable monomer. The crosslinkable monomer is a monomer capable of forming a crosslinked structure during or after polymerization by energy such as heat or light.
[0040] The crosslinkable monomer may be a polyfunctional monomer having two or more polymerization reactive groups. The polyfunctional monomer may be one selected from the group consisting of divinyl compounds such as divinylbenzene, diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, 1,3-butylene glycol diacrylate, and other di(meth)acrylic acid ester compounds, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, and other tri(meth)acrylic acid ester compounds, epoxy group-containing ethylenically unsaturated monomers such as allyl glycidyl ether and glycidyl methacrylate, and combinations of two or more of these.
[0041] In the solid particle, the monomer constituting the polymer of the shell 12 may be the same as or different from the monomer constituting the polymer of the core 11. The types of monomers that can be used are as described above, and are preferably aromatic vinyl monomers, and more preferably styrene derivatives such as styrene and styrene sulfonic acid, but are not limited thereto. If necessary, the polymer of the shell 12 may further include the above-mentioned acid group-containing monomer, crosslinkable monomer, etc.
[0042] The solid particles may include first solid particles having an average particle size of 0.3 μm or less, preferably 0.1 to 0.3 μm, and second solid particles having an average particle size of more than 0.3 μm, preferably more than 0.3 μm to 0.7 μm. The solid particles can contact each other or be bonded by the water-soluble polymer in the adhesive layer of the separator described later, and a large number of pores can be formed by the gaps between the solid particles.
[0043] Among these, the gaps between the second solid particles having a relatively large average particle size may form large pores, and the gaps between the first solid particles having a relatively small average particle size may form small pores. The large pores formed by the gaps between the second solid particles may contribute to the air permeability, ion conductivity, and resistance characteristics of the separator, but may reduce the surface area of the adhesive layer and reduce the adhesiveness of the separator. In this case, the first solid particles may increase the surface area of the adhesive layer to compensate for and improve the adhesiveness reduced by the second solid particles.
[0044] The content of the first solid particles in the water-insoluble polymer may be 20 to 80% by weight, preferably 35 to 70% by weight. If the content of the first solid particles is less than 20% by weight, the adhesiveness may decrease, and if it exceeds 80% by weight, the air permeability, ion conductivity, and resistance properties may decrease.
[0045] The content of the second solid particles in the water-insoluble polymer may be 10 to 30% by weight, preferably 15 to 25% by weight. If the content of the second solid particles is less than 10% by weight, the air permeability, ion conductivity, and resistance properties may decrease, and if it exceeds 30% by weight, the adhesiveness may decrease.
[0046] The solid particles having a core-shell structure can be prepared by stepwise polymerization of the monomers constituting the polymer of the core 11 and the monomers constituting the polymer of the shell 12, while changing the ratio of the monomers.
[0047] Specifically, the monomers constituting the core polymer are mixed with an emulsifier and emulsion polymerized to obtain a particulate polymer constituting the core, and the monomers constituting the shell polymer are added in portions or continuously in the presence of such a particulate polymer and polymerized to obtain solid particles having a core-shell structure.
[0048] Fig. 3(a) is a plan view of an annular hollow particle according to one embodiment of the present invention, and Fig. 3(b) is a cross-sectional view taken along line A-A' in Fig. 3(a). Referring to Fig. 3(a) and Fig. 3(b), the annular hollow particle 20 includes an annular shell 21 having a through hole 22 formed in the center thereof, and the inside of the annular shell 21 may include a filler 23 and a hollow 24.
[0049] The annular hollow particles 20 are analyzed to be produced in the process of producing the solid particles 10 having a core-shell structure, reducing the temperature of the reaction system, and maturing the solid particles for a predetermined time to enlarge the cores of the solid particles. Specifically, when the solid particles are maturated for 3 hours or more, preferably 5 to 30 hours, and more preferably 10 to 24 hours under conditions where the temperature is reduced by 10°C or more compared to the temperature of the reaction system for polymerizing the shell, the core and / or the shell may rupture due to the expansion criticality of the enlarged core, and the annular hollow particles 20 having through holes 22 formed in the center thereof may be produced by such rupture.
[0050] In this manner, since the annular hollow particle 20 is derived from the solid particle 10 having a core-shell structure, the polymer constituting the annular shell 21 and the filler 23 contained therein may be the same as the polymer constituting the shell 12 and the core 11 of the solid particle 10, respectively, and the types of monomers constituting each polymer are as described above.
[0051] The through-holes 22, together with the numerous pores formed by the gaps between the water-insoluble polymer particles, provide a path for ions and / or fluids to pass through the adhesive layer of the separator described below, thereby alleviating the problem of the deterioration of the breathability, ionic conductivity, and resistance properties of the separator caused by the addition of one or more functional layers (heat-resistant layer, adhesive layer, etc.) to one side of a conventional porous base membrane.
[0052] The through-holes 22 formed in the central portions of the annular hollow particles 20 may have an average diameter larger than the average particle size of the first solid particles. If the average diameter of the through-holes 22 is equal to or smaller than the average particle size of the first solid particles, the first solid particles may randomly close the through-holes 22, which may result in a decrease in the air permeability, ion conductivity, and resistance properties of the separator.
[0053] The ratio of the filler 23 inside the annular shell 21 may be 1 to 99% by volume. If the ratio of the filler 23 is less than 1% by volume, the annular hollow particle 20 may easily deform or break, and if it exceeds 99% by volume, the shape of the annular hollow particle cannot be stably maintained due to further expansion of the filler 23 when exposed to an electrolyte.
[0054] The content of the annular hollow particles in the water-insoluble polymer may be 10 to 50% by weight, preferably 20 to 50% by weight, and more preferably 35 to 50% by weight. If the content of the annular hollow particles in the water-insoluble polymer is less than 10% by weight, the air permeability, ion conductivity, and resistance properties of the separator including the adhesive layer may decrease, and if it exceeds 50% by weight, the heat resistance may decrease.
[0055] Another aspect of the present invention provides a separator comprising a porous base membrane and an adhesive layer located on at least one surface of the porous base membrane and comprising the separator coating composition.
[0056] The porous base membrane may be a porous film formed by molding and processing a thermoplastic resin. The porous film may include a large number of pores having a substantially uniform average size, and such pores can contribute to improving the resistance characteristics and ion conductivity of the separator. In addition, since the porous film has high porosity and high mechanical strength, the separator can be thinned to a required thickness.
[0057] The porosity of the porous film may be 30 to 90% by volume, preferably 40 to 80% by volume, and more preferably 40 to 70% by volume. The term "porosity" as used herein means the ratio of the volume of pores to the total volume of any porous article. If the porosity of the porous film is less than 30% by volume, the air permeability and ion conductivity may decrease, and if it exceeds 90% by volume, the mechanical properties such as tensile strength and puncture strength may decrease.
[0058] The average size of the pores in the porous film may be 10 to 100 nm, preferably 20 to 80 nm, and more preferably 30 to 60 nm. If the average size of the pores is less than 10 nm, the air permeability and ion conductivity may decrease, and if it exceeds 100 nm, the mechanical properties such as tensile strength and puncture strength may decrease.
[0059] From the viewpoint of thinning and increasing the energy density of the electrochemical device, the thickness of the porous film may be 5 to 20 μm, preferably 5 to 15 μm, and more preferably 5 to 12 μm. If the thickness of the porous film is less than 5 μm, the mechanical properties may be reduced, and if it exceeds 20 μm, the air permeability and ion conductivity may be reduced.
[0060] The porous film may include a polymer resin having electrical insulation properties, and the polymer resin may include a thermoplastic resin in consideration of shutdown characteristics. The term "shutdown characteristics" used in this specification means that when the battery overheats and the temperature increases, the polymer resin melts and closes the pores of the porous film, thereby blocking the movement of ions. From this perspective, the melting point of the polymer resin or the thermoplastic resin may be 200°C or less.
[0061] The thermoplastic resin may include, for example, one selected from the group consisting of polyethylene, polypropylene, polybutylene, polymethylpentene, ethylene vinyl acetate, ethylene butyl acrylate, ethylene ethyl acrylate, and combinations or copolymers of two or more of these, and may preferably include at least one of polyethylene and polypropylene, and more preferably may include polyethylene.
[0062] The polyethylene may be one selected from the group consisting of ultra-high molecular weight polyethylene (UHMWPE, Mw: 1,000,000 to 7,000,000 g / mol), high molecular weight polyethylene (HMWPE, Mw: 100,000 to 1,000,000 g / mol), high density polyethylene (HDPE, Mw: 100,000 to 1,000,000 g / mol), low density polyethylene (LDPE, Mw: 10,000 to 100,000 g / mol), homogeneous linear and linear low density polyethylene (LLDPE), and a combination of two or more of these.
[0063] For example, the polyethylene has a weight average molecular weight M w The polyethylene may be a high density polyethylene having a weight average molecular weight of 250,000 to 450,000. If the weight average molecular weight of the polyethylene exceeds 450,000, the viscosity may become high and the processability may decrease, and if it is less than 250,000, the viscosity becomes too low and the dispersibility with the pore-forming agent, antioxidant, etc. used in producing the porous film may decrease drastically, and in some cases, phase separation or layer separation may occur.
[0064] The porous base membrane may further include a heat-resistant layer having the porous film as a substrate and located on at least one surface of the substrate and including a plurality of inorganic particles bound by a binder. The heat-resistant layer may include a large number of pores formed by gaps between adjacent inorganic particles, and the average size of the pores may be substantially uniform.
[0065] The content of the inorganic particles in the heat-resistant layer may be 60 to 99% by weight. If the content of the inorganic particles is less than 60% by weight, a required level of heat resistance cannot be imparted, and if it exceeds 99% by weight, the air permeability, ion conductivity, and resistance characteristics of the separator may decrease, the dispersibility of the inorganic particles may decrease, and the workability and processability during slurry coating may decrease.
[0066] The average particle size of the inorganic particles may be larger than the average size of the pores in the porous film. If the average particle size of the inorganic particles is equal to or smaller than the average size of the pores in the porous film, the inorganic particles may penetrate into the pores of the porous film and close the pores, thereby significantly reducing the air permeability and ion conductivity of the separator. The average particle size of the inorganic particles may be, but is not limited to, 100 to 1,000 nm, preferably 200 to 800 nm, and more preferably 400 to 800 nm.
[0067] The thickness of the heat-resistant layer may be 0.1 to 5 μm. If the thickness of the heat-resistant layer is less than 0.1 μm, a necessary level of heat resistance cannot be imparted, whereas if the thickness exceeds 5 μm, the separator becomes too thick, which can hinder miniaturization and integration of electrochemical devices.
[0068] The inorganic particles may be, for example, one selected from the group consisting of SiO2, AlO(OH), Mg(OH)2, Al(OH)3, TiO2, BaTiO3, Li2O, LiF, LiOH, Li3N, BaO, Na2O, Li2CO3, CaCO3, LiAlO2, Al2O3, SiO, SnO, SnO2, PbO2, ZnO, P2O5, CuO, MoO, V2O5, B2O3, Si3N4, CeO2, Mn3O4, Sn2P2O7, Sn2B2O5, Sn2BPO6, and combinations of two or more thereof, and preferably may be AlO(OH), but is not limited thereto.
[0069] The binder can be melted and fused in the heat-resistant layer to bond the inorganic particles to each other as well as to the porous substrate. The binder can be a water-soluble polymer. The water-soluble polymer can be, for example, one selected from the group consisting of polyacrylic acid, polyvinylpyrrolidone, polyvinyl acetate, polyimide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, hydroxyethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, polyvinyl alcohol, polyethylene oxide, polyethylene glycol, and a combination of two or more of these, preferably polyvinyl alcohol, but is not limited thereto.
[0070] At least one surface of the porous base membrane may be provided with an adhesive layer made of the separator coating composition, which can improve the bonding strength between the separator and the electrodes, thereby contributing to improving the electrochemical properties and life characteristics of the battery.
[0071] The adhesive layer may be made of a separator coating composition including the water-soluble polymer and the water-insoluble polymer, and may have a structure in which the water-insoluble polymer having a particulate form is bound by the water-soluble polymer. The water-soluble polymer and the water-insoluble polymer may be uniformly dispersed in the adhesive layer.
[0072] The adhesive layer may include a number of pores formed by the gaps between adjacent water-insoluble polymer particles, i.e., organic particles, and the average size of the pores may be substantially uniform. In addition, a part of the water-insoluble polymer is composed of annular hollow particles having a through hole formed in the center, and the through hole, together with the number of pores formed by the gaps between the organic particles, provides a path through which ions and / or fluids can pass through the adhesive layer, so that the problem of the air permeability, ion conductivity, and resistance properties of the separator being reduced by adding one or more functional layers (heat-resistant layer, adhesive layer, etc.) to one side of the conventional porous base membrane can be alleviated.
[0073] The content of the organic particles in the adhesive layer may be 50 to 99% by weight. If the content of the organic particles is less than 50% by weight, a required level of adhesiveness cannot be imparted, and if it exceeds 99% by weight, the air permeability and ion conductivity of the separator may decrease, the dispersibility of the organic particles may decrease, and workability and processability during coating may decrease.
[0074] When the adhesive layer is located on the surface of the heat-resistant layer, the average particle size of the organic particles may be smaller than the average particle size of the inorganic particles contained in the heat-resistant layer. If the average particle size of the organic particles is equal to or larger than the average particle size of the inorganic particles, the average pore size of the adhesive layer may be larger than the average particle size of the inorganic particles. In this case, as the heat-resistant layer is continuously exposed to the electrolyte inside the battery, the inorganic particles may be partially and continuously detached from the porous substrate, and the heat resistance of the separator may gradually decrease.
[0075] The thickness of the adhesive layer may be 0.5 to 1.5 μm. If the thickness of the adhesive layer is less than 0.5 μm, the adhesiveness may be reduced, and the inorganic particles contained in the heat-resistant layer may not be effectively prevented from being exposed to the electrolyte. On the other hand, if the thickness of the adhesive layer is more than 1.5 μm, the air permeability, ion conductivity, and resistance characteristics may be reduced, and the separator may become thick, which may hinder miniaturization and integration of the electrochemical device.
[0076] If necessary, the adhesive layer may further contain inorganic particles like the heat-resistant layer in order to enhance the heat resistance of the separator. The weight ratio of the organic particles and the inorganic particles in the adhesive layer may be 1:50 to 80. If the content of the inorganic particles is too low, the required level of heat resistance cannot be imparted, and if it is too high, the dispersibility of the inorganic particles may decrease, or the workability and processability during coating may decrease.
[0077] The water-soluble polymer can be melted and fused in the adhesive layer to bond the organic particles to each other, or, if the adhesive layer contains a certain amount of inorganic particles, to bond the inorganic particles to each other, or to bond the organic and inorganic particles to each other, and can also bond the organic particles and / or the inorganic particles to the heat-resistant layer. The types of water-soluble polymer that can be used are as described above for the binder of the heat-resistant layer.
[0078] The ratio of the thickness of the adhesive layer to the thickness of the heat-resistant layer may be 0.15 to 0.5. If the ratio of the thickness of the adhesive layer to the thickness of the heat-resistant layer is out of the above range, it is difficult to achieve a balanced heat resistance, adhesion, air permeability, ion conductivity, and resistance properties of the separator. Specifically, if the ratio of the thickness of the adhesive layer to the thickness of the heat-resistant layer is less than 0.15, the air permeability and resistance properties may be improved, and the heat resistance and adhesion may be reduced. On the other hand, if the thickness ratio exceeds 0.5, the air permeability and resistance properties may be reduced, and the heat resistance and adhesion may be improved.
[0079] Generally, when the thickness and / or surface density (weight / unit area) of the heat-resistant layer and / or adhesive layer coated on the surface of the porous film increases, the heat resistance and adhesiveness improve, whereas the breathability and resistance properties tend to deteriorate. That is, "heat resistance and adhesiveness" and "breathability and resistance properties" are in a so-called trade-off relationship, which is difficult to achieve with each other.
[0080] In contrast, the separator according to the present invention can achieve a balanced combination of heat resistance, adhesiveness, breathability, and ionic conductivity by forming a portion of the organic particles contained in the adhesive layer, i.e., the water-insoluble polymer, in the form of ring-shaped hollow particles with through-holes formed in the center. Specifically, the through-holes, together with a large number of pores formed by the gaps between the organic particles, provide a path through which ions and / or fluids can pass through the adhesive layer, thereby alleviating the problem of the separator's breathability, ionic conductivity, and resistance characteristics being reduced by adding one or more functional layers (heat-resistant layer, adhesive layer, etc.) to one side of the conventional porous base membrane.
[0081] In addition, the porous film is hydrophilized to ensure sufficient wettability of the aqueous slurry when the aqueous slurry is coated to form the heat-resistant layer and / or the adhesive layer, thereby improving the bonding strength between the porous film and the heat-resistant layer and / or the adhesive layer. The hydrophilized porous film may have a contact angle with water (H2O) of 15° or less, and the absolute value of the zeta potential measured at a negative value (-) on the surface of the porous film may be 10 mV or more, preferably 15 mV or more, and more preferably 20 mV or more.
[0082] The hydrophilized porous film has hydrophilic functional groups, e.g., -SO3 groups, formed on the surface and the surface of the internal pores, which have hydrophilicity, and can easily bond to the heat-resistant layer and / or the adhesive layer due to high affinity with the slurry, which is essentially hydrophilic, and can also strengthen the bonding force, so that the durability of the separator can be significantly improved, and the loss of the hydrophilic groups contained in the porous film and / or the inorganic particles of the heat-resistant layer and the organic particles of the adhesive layer can be prevented, so that the breathability, ion conductivity, heat resistance, and adhesion can be improved.
[0083] The separator can satisfy one or more of the following conditions (i) to (v), preferably all of the conditions (i) to (v). (i) Fs ≤ 190 sec / 100 ml (Fs is the air permeability of the separator), (ii) Rs ≤ 100 mΩ (Rs is the resistance of the separator), (iii) the longitudinal thermal shrinkage rate at 150 °C is 2.5% or less, (iv) 0 sec / 100 ml < Fs - Fb ≤ 20 sec / 100 ml (Fb is the air permeability of the base film), (v) 0 mΩ < Rs - Rb ≤ 10 mΩ (Rb is the resistance of the base film).
[0084] The air permeability Fs of the separator is 190 sec / 100 ml or less, preferably 150 to 185 sec / 100 ml, more preferably 160 to 180 sec / 100 ml. The resistance Rs of the separator is 100 mΩ or less, preferably 95 mΩ or less, more preferably 80 to 92 mΩ. The longitudinal (MD) thermal shrinkage rate of the separator at 150 °C is 2.5% or less, preferably 2.2% or less. The difference Fs - Fb between the air permeability Fs of the separator and the air permeability Fb of the base film is 0 to 20 sec / 100 ml, preferably 0 to 15 sec / 100 ml, more preferably 1 to 10 sec / 100 ml. The difference Rs - Rb between the resistance Rs of the separator and the resistance Rb of the base film is 0 to 10 mΩ, preferably 0 to 7 mΩ, more preferably 0 to 4 mΩ.
[0085] Hereinafter, embodiments of the present invention will be described in detail.
[0086] Manufacturing Example 1 Into a pressure vessel with a stirrer and a pressure resistance of 5 MPa, 75 parts by weight of methyl methacrylate as a (meth)acrylic acid ester monomer for forming the core of solid particles, 4 parts by weight of methacrylic acid as a (meth)acrylic acid monomer, 1 part by weight of ethylene glycol dimethacrylate (EDMA) as a crosslinkable monomer, 1 part by weight of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts by weight of ion-exchanged water, and 0.5 part by weight of potassium persulfate as a polymerization initiator were added. After sufficiently stirring, the temperature was raised to 60 °C to initiate polymerization.
[0087] When the polymerization conversion rate reached 96%, 19 parts by weight of styrene as an aromatic vinyl monomer for forming the shell of the solid particles and 1 part by weight of methacrylic acid as an acid group-containing monomer were continuously added, the temperature was raised to 70°C, and the polymerization was continued.
[0088] When the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 24 hours to increase the average particle size of the synthesized solid particles and obtain an aqueous dispersion in which some of the solid particles were converted to annular hollow particles. Polyvinyl alcohol was added to the aqueous dispersion and diluted with water to a solid content of 5 wt% to prepare a coating composition. The polyvinyl alcohol content in the solid content was 5 wt%.
[0089] Manufacturing Example 2 When the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 20 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles. A coating composition was prepared in the same manner as in Preparation Example 1, except that the mixture was cooled to 60°C and aged for 20 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles.
[0090] Production Example 3 When the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 16 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles. A coating composition was prepared in the same manner as in Preparation Example 1, except that the mixture was cooled to 60°C and aged for 16 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles.
[0091] Production Example 4 When the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 14 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles. A coating composition was prepared in the same manner as in Preparation Example 1, except that the mixture was cooled to 60°C and aged for 14 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles.
[0092] Production Example 5 When the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 8 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles. A coating composition was prepared in the same manner as in Preparation Example 1, except that the mixture was cooled to 60°C and aged for 8 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles.
[0093] Comparative Manufacturing Example 1 Into a 5 MPa pressure vessel equipped with a stirrer, 75 parts by weight of methyl methacrylate as a (meth)acrylic acid ester monomer for forming the core of solid particles, 4 parts by weight of methacrylic acid as a (meth)acrylic acid monomer, 1 part by weight of ethylene glycol dimethacrylate (EDMA) as a cross-linking monomer, 1 part by weight of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts by weight of ion-exchanged water, and 0.5 parts by weight of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the mixture was heated to 60°C to initiate polymerization.
[0094] When the polymerization conversion rate reached 96%, 19 parts by weight of styrene as an aromatic vinyl monomer for forming the shell of the solid particles and 1 part by weight of methacrylic acid as an acid group-containing monomer were continuously added, and the temperature was raised to 70° C. to continue polymerization. When the polymerization conversion rate of all added monomers reached 96%, the reaction was stopped to obtain an aqueous dispersion containing solid particles, which was diluted with water so that the solid content of the aqueous dispersion was 5% by weight, and a trace amount of a surfactant was added to produce a coating composition.
[0095] Comparative Manufacturing Example 2 A coating composition was prepared in the same manner as in Preparation Example 1, except that when the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 5 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which a part of the solid particles was converted into ring-shaped hollow particles.
[0096] Comparative Manufacturing Example 3 When the polymerization conversion rate of all added monomers reached 96%, the mixture was cooled to 60°C and aged for 30 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles. A coating composition was prepared in the same manner as in Preparation Example 1, except that the mixture was cooled to 60°C and aged for 30 hours to increase the average particle size of the synthesized solid particles and to obtain an aqueous dispersion in which some of the solid particles were converted to ring-shaped hollow particles.
[0097] Experimental Example 1 The compositions of the solid particles and hollow annular particles in each of the aqueous dispersions obtained in the Production Examples and Comparative Production Examples were analyzed and are shown in the following Table 1. In the case of the solid particles, those having an average particle size of 0.3 μm or less were classified as first solid particles, and those having an average particle size of more than 0.3 μm were classified as second solid particles, and the composition of each was analyzed.
[0098] [Table 1]
[0099] Fig. 4 shows SEM images of the aqueous dispersions of Preparation Examples and Comparative Preparation Examples. Referring to Fig. 4, solid particles and annular hollow particles were observed in all of the aqueous dispersions of Preparation Examples 3 and 5, whereas the annular hollow particles observed in Preparation Examples 3 and 5 were not observed in the aqueous dispersion of Comparative Preparation Example 1.
[0100] Example 1 A ceramic slurry was prepared by mixing and uniformly dispersing solids containing 95% by weight of boehmite (AlOOH) with an average particle size of 500 nm, 3% by weight of acrylonitrile copolymer, and 2% by weight of polyvinyl alcohol and distilled water in a weight ratio of 20:80.
[0101] The ceramic slurry was bar-coated to a thickness of 3 μm on one side of a 9 μm-thick polyethylene porous substrate (air permeability: 110 sec / 100 ml) and then dried to obtain a base film including a heat-resistant layer.
[0102] The coating composition obtained in Preparation Example 1 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm, and then dried to obtain a separator including a porous substrate / heat-resistant layer / adhesive layer in that order.
[0103] Example 2 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Preparation Example 2 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0104] Example 3 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Preparation Example 3 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0105] Example 4 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Preparation Example 4 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0106] Example 5 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Preparation Example 5 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0107] Comparative Example 1 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Comparative Preparation Example 1 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0108] Comparative Example 2 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Comparative Preparation Example 2 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0109] Comparative Example 3 A separator including a porous substrate / heat-resistant layer / adhesive layer in that order was obtained in the same manner as in Example 1, except that the coating composition obtained in Comparative Preparation Example 3 was bar-coated on the heat-resistant layer to a thickness of 0.5 μm and then dried.
[0110] Experimental Example 2 The test methods for each of the physical properties measured in the present invention are as follows. Unless otherwise specified regarding temperature, measurements were performed at room temperature (25° C.).
[0111] The properties of the base membrane and separator test pieces prepared in the above examples and comparative examples were measured, and the results are shown in Tables 2 and 3 below. -Air permeability (Gurley, sec / 100ml): Using Asahi Seiko Co., Ltd.'s Gurley Densometer EGO2-5 model, the time it takes for 100ml of air to pass through the base membrane and separator test pieces with a diameter of 29.8mm at a measurement pressure of 0.025MPa was measured. -Resistance (mΩ): An electrolyte was prepared by dissolving LiPF6 at 1 molar concentration in a solvent that was a mixture of ethylene carbonate, propylene carbonate, and propyl propionate in a ratio (volume ratio) of 25:10:65. After immersing each separator in the electrolyte, a coin cell was made and the resistance was measured using EIS (Electrochemical impedance spectroscopy) equipment. -Heat shrinkage rate (%): A separator test piece having a size of 200 x 200 mm was placed between A4 sheets of paper and left in an oven at 150°C for 1 hour, and then cooled to room temperature. The shrinkage length of the test piece in the machine direction (MD) was measured, and the heat shrinkage rate was calculated according to the following formula. Heat shrinkage rate (%) = (l3-l4) / l3 x 100 (In the above formula, l3 is the longitudinal length of the test piece before shrinkage, and l4 is the longitudinal length of the test piece after shrinkage.)
[0112] [Table 2]
[0113] [Table 3]
[0114] The above description of the present invention is for illustrative purposes only, and those skilled in the art will understand that the present invention can be easily modified in other specific forms without changing the technical idea or essential features of the present invention. Therefore, the above-described embodiments and examples should be understood to be illustrative in all respects and not restrictive. For example, each component described as a single type can be implemented in a distributed form, and similarly, each component described as a distributed type can be implemented in a combined form.
[0115] The scope of the present invention is defined by the claims set forth below, and all modifications and variations that fall within the meaning and scope of the claims and their equivalent concepts should be construed as being included within the scope of the present invention. [Explanation of symbols]
[0116] 10 Solid Particles 11 cores 12. Shell 20 Annular hollow particles 21 Annular Shell 22 Through hole 23 Filling material 24 Hollow
Claims
1. 1. A separator coating composition comprising a water soluble polymer and a water insoluble polymer, The water-insoluble polymer includes solid particles and hollow ring particles, The solid particles have a core-shell structure including a core and a shell covering at least a portion of the surface of the core, The annular hollow particle includes an annular shell having a through hole formed in the center thereof, the interior of the annular shell includes a filler and a hollow; A separator coating composition, wherein the content of the annular hollow particles in the water-insoluble polymer is 10 to 50% by weight.
2. 2. The separator coating composition of claim 1, wherein the percentage of the filler inside the annular shell is 1 to 99 volume percent.
3. a porous base membrane; and an adhesive layer located on at least one surface of the porous base membrane, the adhesive layer comprising the separator coating composition of claim 1 or 2.
4. The separator according to claim 3 , wherein the porous base membrane comprises a porous substrate and a heat-resistant layer located on at least one surface of the porous substrate and including a plurality of inorganic particles bound together by a binder.
5. The separator according to claim 3, which satisfies one or more of the following conditions (i) to (v): (i) Fs≦190 sec / 100 ml or less (Fs is the air permeability of the separator); (ii) Rs≦100 mΩ, where Rs is the resistance of the separator; (iii) a longitudinal heat shrinkage rate of 2.5% or less at 150°C; (iv) 0 sec / 100 ml<Fs-Fb≦20 sec / 100 ml (Fb is the air permeability of the base membrane); (v) 0 mΩ<Rs-Rb≦10 mΩ, where Rb is the resistance of the base film.
Citation Information
Patent Citations
Separator for power storage device, and electrochemical element
JP2016072197A
Particle external additive for e-paper for composite surface treatment using carbonblack,sio2 and particle for e-paper treated composite surface using thereof
KR1020120117249A
Composition for producing protective film, protective film, and electricity storage device
WO2014041983A1